Loss of heterozygosity in tuberous sclerosis hamartomas. Issue 11 (November 1996) - Sepp, T; Yates, J R; Green, A J
Abstract : We have previously described in tuberous sclerosis (TSC) hamartomas the phenomenon of loss of heterozygosity (LOH) for DNA markers in the region of both the TSC2 gene on chromosome 16p13.3 and the TSC1 gene on 9q34. We now describe the spectrum of LOH in 51 TSC hamartomas from 34 cases of TSC. DNA was extracted from leucocytes or normal paraffin embedded tissue, and from frozen paraffin embedded hamartoma tissue from the same patient. The samples were analysed for 11 markers spanning the TSC1 locus and nine markers spanning the TSC2 locus. Twenty-one of 51 hamartomas showed LOH (41%). There was significantly more LOH on 16p13.3, with 16 hamartomas showing LOH around TSC2, and five in the vicinity of TSC1. No hamartoma showed LOH for markers around both loci. All the areas of LOH on chromosome 9 were large, but the smallest region of overlap lay between the markers D9S149 and D9S114, providing independent evidence for the localisation of the TSC1 gene. These data show that LOH is a common finding in a wide range of hamartomas, affecting the same TSC locus in different lesions from the same patient but not affecting both loci. These data support the hypothesis that both the TSC genes act as tumour suppressors and that the manifestations of TSC in patients with germline TSC mutations rise from "second hit" somatic mutations inactivating the remaining normal copy of the TSC gene.